2017
DOI: 10.1159/000477362
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Challenges in the Care of Refugees with End-Stage Renal Disease: What Western Nephrologists Should Know

Abstract: Forced migration is on the rise, mainly from the Middle East to western countries, resulting in unprecedented moral, political, and economic challenges for both refugees and host communities. Recent research showed that refugees represent around 1.5% of the dialysis population in several European and Middle Eastern countries surveyed. Despite the fact that refugees represent a small percentage of all dialysis patients in these countries, adequate care for this population is challenging. There are cultural diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…ongoing conflicts and wars, 2 refugee crises and differences in language, 3 religious practices/beliefs, 4 and culture. 5 One study suggested the presence of additional, less obvious challenges, including variable availability of infrastructure, constraints on health expenditure related to gross national income, lack of data on kidney disease, and low-level awareness within the medical community and the public about the advances of therapeutic and preventive measures to reduce KF. 6 Regional bodies, such as the Middle East Society for Organ Transplantation, have been formed as a platform for filling the gaps and improving education, training, research, and collaboration within the region.…”
mentioning
confidence: 99%
“…ongoing conflicts and wars, 2 refugee crises and differences in language, 3 religious practices/beliefs, 4 and culture. 5 One study suggested the presence of additional, less obvious challenges, including variable availability of infrastructure, constraints on health expenditure related to gross national income, lack of data on kidney disease, and low-level awareness within the medical community and the public about the advances of therapeutic and preventive measures to reduce KF. 6 Regional bodies, such as the Middle East Society for Organ Transplantation, have been formed as a platform for filling the gaps and improving education, training, research, and collaboration within the region.…”
mentioning
confidence: 99%
“…As chronic kidney disease progresses, patients often need to make lifestyle changes, which can result in considerable psychological stress [ 32 ]. In the process of caring for HD patients, the participants of this study observed and clarified that the “refusal” of dialysis behavior was a manifestation of unacceptance exhibited by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients require comprehensive education about their RRT options. Adequate communication between healthcare professionals and patients is crucial when assisting patients in accepting dialysis [ 32 ]. In this study, the participants recognized that effective communication, employing language aligned with the patient’s cultural conventions and values, played a pivotal role in helping patients accept the realities of HD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culture plays a significant role in influencing the health behavior, disease cognition, response, and medical-seeking behavior of ESRD patients [10]. Taiwan is a multicultural society comprising diverse Han subgroups, as well as indigenous Malayo-Polynesian peoples and immigrants from all over the world [11].…”
Section: Introductionmentioning
confidence: 99%